Dimitri Germidis. El trabajo y las relaciones laborales en la industria mexicana de la construcción. México : El Colegio de México, 1974. 138 p. - Zapata, Francisco (El Colegio de México A.C., 1976)
DIMITRO GERMIDIS, El trabajo y las relaciones laborales en la industria mexicana de la construcción; El Colegio de México, 1974.